2017
DOI: 10.1002/ffj.3397
|View full text |Cite
|
Sign up to set email alerts
|

Identification of isobutyl angelate, isoamyl angelate and 2‐methylbutyl isobutyrate as active constituents in Roman chamomile essential oil that promotes mouse ambulation

Abstract: Roman chamomile (Chamaemelum nobile or Anthemis nobilis) has traditionally been used for health care, health maintenance and medicinal purposes, and the essential oil obtained from the flowers is used as a basic ingredient for aromatherapy. Roman chamomile essential oil (CHA) produces psychostimulant‐like effects, such as the ambulation‐promoting effect, on mouse behaviour. However, mechanisms underlying the effects of CHA remain unclear. The present study aimed to identify the constituents responsible for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…Moreover, calming effects are also produced by increasing serotonin levels while decreasing glucocorticoids like in the case of ylang‐ylang EO (Zhang, Zhang, Feng, & Yao, 2016; Zhang, Zhang, Feng, & Yao, 2018). Furthermore, it has been demonstrated experimentally that other EOs like rosemary (Moss, Cook, Wesnes, & Duckett, 2003; Villareal et al, 2017), clary sage (Seol et al, 2010), and roman chamomile (Umezu, 2012; Umezu, Sano, Hayashi, Yoshikawa, & Shibata, 2017) stimulate the DAnergic system resulting in psychostimulant and cognitive‐enhancer effects. Additionally, bergamot (Morrone et al, 2007), lemongrass (Costa et al, 2011) and lavender (Guillmain, Rousseau, & Delaveau, 1989) EOs can exert its anxiolytic effects by activating the GABAergic system.…”
Section: Actions Of Eos On the Central Nervous Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, calming effects are also produced by increasing serotonin levels while decreasing glucocorticoids like in the case of ylang‐ylang EO (Zhang, Zhang, Feng, & Yao, 2016; Zhang, Zhang, Feng, & Yao, 2018). Furthermore, it has been demonstrated experimentally that other EOs like rosemary (Moss, Cook, Wesnes, & Duckett, 2003; Villareal et al, 2017), clary sage (Seol et al, 2010), and roman chamomile (Umezu, 2012; Umezu, Sano, Hayashi, Yoshikawa, & Shibata, 2017) stimulate the DAnergic system resulting in psychostimulant and cognitive‐enhancer effects. Additionally, bergamot (Morrone et al, 2007), lemongrass (Costa et al, 2011) and lavender (Guillmain, Rousseau, & Delaveau, 1989) EOs can exert its anxiolytic effects by activating the GABAergic system.…”
Section: Actions Of Eos On the Central Nervous Systemmentioning
confidence: 99%
“…Although diverse extracts of roman chamomile are well‐known for their anxiolytic and sedative activities, a recent study has shown that the EO produced by steam distillation has psychostimulant effects. Umezu et al, 2017 identified and studied the effects of Roman chamomile EO constituents on the CNS in male mice by using the tilting type ambulometer test (Table 2). Isobutyl angelate, isoamyl angelate and 2‐methylbutyl isobutyrate were identified as the major active constituents responsible for the ambulatory‐promoting effects of roman chamomile, which accounted for about 75% of the EO.…”
Section: Actions Of Eos On the Central Nervous Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…GC/MS analysis was performed using an MStation JMS-700KII mass spectrometer (JEOL, Tokyo, Japan) equipped with a 6890 N gas chromatograph (GC; Agilent Technologies, Santa Clara, CA) [ 19 ]. The GC was fitted with a fused silica capillary column (DB-5MS; 0.25 mm inner diameter, 30 m) coated with 5% phenyl methyl silica.…”
Section: Methodsmentioning
confidence: 99%